Hábitos alimentarios, depresión, consejería y estado nutricional en pacientes con tuberculosis pulmonar en IPRESS de la provincia de Maynas - Fachin Gómez, Pamela Milagros (2024)
The present research titled "Eating habits, depression, counseling and nutritional status in patients with Pulmonary Tuberculosis in IPRESS of the province of Maynas." Objective: Determine the relationship between eating habits, depression, counseling and nutritional status in patients with Pulmonary Tuberculosis in IPRESS in the province of Maynas. Method: The study has a quantitative approach, non experimental, uses a descriptive correlational and cross-sectional design. The sample used in the study was made up of 90 patients with pulmonary tuberculosis, 38 female and 52 male, judged between 18 and 59 years old, from 4 IPRESS in the province of Maynas. Results: Surveys were given to patients, who were asked to answer each question according to their criteria. According to nutritional status indicators, patients showed a normal nutritional status of 47% according to BMI, followed by a diagnosis of overweight with 27% and obesity with 13%. When hemoglobin levels were measured, 57% of patients did not have anemia and 30% had mild anemia. Regarding eating habits, patients marked the foods they consumed daily, weekly, or monthly; As a consequence, 64% of the patients' eating habits were inadequate. On the Zung test questionnaire, patients marked their mood during the last week, 64.4% of patients were not depressed, while 33.3% of patients were slightly depressed. On the other hand, patients indicated that nutritional counseling was inadequate and that they did not receive adequate nutritional information at each counseling session. In addition, they indicated that nutritional counseling was carried out every semester. Conclusion: Sufficient statistical evidence was found between nutritional status, eating habits and depression. However, no statistical evidence was found to support the relationship between nutritional status and nutritional counseling.